Syair sebagai Media Keagamaan: Analisis Nilai Filosofis-Religius Syair “Cokot Boyo” dalam Konteks Keberagamaan Masyarakat Indonesia Kontemporer - Masamah, Ulfa (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2018)
This paper examines the diversity of Indonesian Islam which experiences a shifting paradigm from anthropocentric-historical to theocentric-normative. This movement has ruled out the basic message of culture and locality that was taught by predecessors, such as the Cokot Boyo poem and so on. This study is a literature review that examines some primary literature related to the theme that is assumed, resulting in a conclusion that the emergence of the poem as a response to culture that has paid attention to the importance of learning religion, such as developments at this time, Muslim society tends to learn quickly and no matter learned. This is different from the guardians who have taught the science of religion for quite a long time. The difference lies in the duration and competence of religious knowledge possessed, but the religious authorities have switched to ustaz-ustaz who seem clever to bring religious sources. In this region this paper discusses the religious patterns of the Indonesian Islamic community.